Financial Sources for European Green Deal - Karel Janda; Lucia Sajdikova (ZBW – Leibniz Information Centre for Economics, 2022)
This paper provides a descriptive analysis of financing the European Green Deal. It is focused on the description of financial resources used for financing the Green Deal. The first part identifies public financing supporting the green economy, including incentive schemes, subsidies and taxes related supports. The second part identifies commercial funding available for climate transition, including green bonds and other climate and sustainability bonds and related loan schemes. While the first two chapters are covered on the level of the whole European Union, the last chapter is focused on the Czech Republic.
Keywords: 330